Peran Orang Tua dalam Upaya Pencegahan Kekerasan Seksual Pranikah pada Remaja - Supiani; Ernawati (ProHealth Journal, 2026)
Sexual violence among adolescents remains a serious issue that requires close attention due to its potential physical, psychological, and social impacts. Several factors increase adolescents’ vulnerability to sexual violence, including limited parental supervision, poor communication within the family, and a lack of sexual education provided at home. Parents play a crucial role in shaping adolescents’ knowledge, attitudes, and behaviors by providing sexual education, instilling moral values, and monitoring their social environment as well as their use of social media. This article aims to analyze the role of parents in preventing sexual violence among adolescents through a literature review approach. The review was conducted by examining five scholarly articles published between 2020 and 2025. The findings indicate that open communication between parents and children, early sexual education, emotional support, and effective supervision contribute to increasing adolescents’ awareness of sexual violence risks and reducing their vulnerability to such incidents. Conversely, low parental involvement may increase adolescents’ susceptibility to various forms of sexual violence. Therefore, strengthening parental roles is essential in creating a safe, supportive, and educational family environment as a preventive measure against sexual violence among adolescents.